Chenopodium giganteum D. Don (Chenopodiaceae), una nueva especie exótica para la flora vascular de Chile - CORDERO, SEBASTIÁN; GÁLVEZ, FRANCISCA (Gayana Botánica, 2018)
Chenopodium giganteum D. Don is described as a new alien plant species in the Chilean vascular flora. A brief description, illustrations and an identification key for alien species of the genus Chenopodium L. present in Chile are provided.